English Club to Develop English Language Skills: A Case Study of An Elementary School in Indonesia - Rendra Ari Ekawati; Rina Febrina Sarie (Nur Science Institute, 2021)
Background: This study aims to describe: (1) English Club background at SDIT (Islamic Elementary School) Az-Zahra Sragen (2) English Club planning, (3) English Club implementation, (4) English Club implementation constraints, (5) Solutions to overcome English Club implementation constraints, (6) Evaluation of English Club at SDIT Az-Zahra Sragen. Method: Types of research this is qualitative descriptive research with a case study design. The informants of this research are the principal, English Club supervisor, English teacher class 3,4,5, English Club students. Data collection techniques used are interviews, observation, and documentation. The technique of checking the validity of the data is done by triangulation of sources. The data were analyzed through data collection, reduction, display, and conclusion. Results: This shows various information about the English Club at SDIT Az-Zahra Sragen in developing English language skills. The data obtained include The background of the English Club, namely so that students can speak English fluently and communicate correctly using English. In addition, it is also motivated for competition. English Club planning includes socialization, ideas and financing, planning before implementation, and student preparation. Implementation of the English Club includes materials, media, techniques, and activities. Meanwhile, English skills that are more prominent are speaking skills. There are still obstacles to be faced. The obstacles and solutions include: when making materials, designing activities, media, implementation, in developing English skills.